2015
DOI: 10.1128/aem.01798-15
|View full text |Cite
|
Sign up to set email alerts
|

FleQ Coordinates Flagellum-Dependent and -Independent Motilities in Pseudomonas syringae pv. tomato DC3000

Abstract: bMotility plays an essential role in bacterial fitness and colonization in the plant environment, since it favors nutrient acquisition and avoidance of toxic substances, successful competition with other microorganisms, the ability to locate the preferred hosts, access to optimal sites within them, and dispersal in the environment during the course of transmission. In this work, we have observed that the mutation of the flagellar master regulatory gene, fleQ, alters bacterial surface motility and biosurfactant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
51
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(62 citation statements)
references
References 93 publications
(149 reference statements)
5
51
0
Order By: Relevance
“…However, putative swarming motility was likely downregulated at 28 °C but was compensated for by twitching motility in Pto. Specifically, we found that Pto has an additional fliC- and cheA2 -dependent surface motility mechanism as previously shown (Nogales et al, 2015), which is active only at higher temperatures. pilA was essential for surface motility at 28 °C and fliC and cheA2 were essential for surface motility at 21 °C (Fig.…”
Section: Discussionsupporting
confidence: 86%
“…However, putative swarming motility was likely downregulated at 28 °C but was compensated for by twitching motility in Pto. Specifically, we found that Pto has an additional fliC- and cheA2 -dependent surface motility mechanism as previously shown (Nogales et al, 2015), which is active only at higher temperatures. pilA was essential for surface motility at 28 °C and fliC and cheA2 were essential for surface motility at 21 °C (Fig.…”
Section: Discussionsupporting
confidence: 86%
“…These results suggest a negative regulation of syfR and therefore also of the syf operon by FleQ. Additionally, in plant experiments the fleQ syfA double mutant showed diminished disease symptoms suggesting that sliding contributes to P. syringae colonization of the leaf surface, a habitat where flagella‐dependent movement might not be optimal (Nogales et al ., ).…”
Section: Growth and Surfactant Dependent Sliding (Group I)mentioning
confidence: 97%
“…P. syringae uses another lipopeptide, syringafactin to reduce the surface tension and thereby facilitate passive movement. While investigating the regulation of motility in P. syringae, Nogales et al discovered that a fleQ mutant lacking the proposed master regulator of motility can spread over semi-solid agar in a distinct pattern despite lacking flagella (Nogales et al, 2015). This spreading was proposed to be sliding motility based on its flagellum-independency.…”
Section: Growth and Surfactant Dependent Sliding (Group I)mentioning
confidence: 99%
See 1 more Smart Citation
“…syringae (Hockett et al 401 2013), surface motility of wild type Pto was not markedly affected at 28 o C compared to 21 o C. 402 However, putative swarming motility was likely downregulated at 28 o C but was compensated for 403 by twitching motility in Pto. Specifically, we found that Pto has an additional fliC-and cheA2-404 dependent surface motility mechanism as previously shown (Nogales et al 2015), which is 405 active only at higher temperatures. pilA was essential for surface motility at 28 o C and fliC and 406 cheA2 were essential for surface motility at 21 o C (Figure 5) revealing that Pto has at least two 407 genetically distinct mechanisms for surface motility, both of which are cheA1-independent.…”
supporting
confidence: 56%